The health tourism in the state of Hidalgo, Mexico - Gracia Hernández, Maximiliano (2017)
The target of this study was to determine the strengths, weaknesses, opportunities and threats that there has the tourist area of resorts Ixmiquilpan - Tasquillo, the previous thing managed to be discovered from afield study in situ, accompanied by a series of interviews answered by visitors and tourists to its exit of thetourist area. The research technique was based on the application of forty interviews. Derivative of the investigation we show the results and the reality of the spas in the tourist area of Ixmiquilpan-Tasquillo in Hidalgo State. The results show that the tourist area Ixmiquilpan - Tasquillo not has the secondary services that allow them to be exploited effectively and efficiently. It is necessary to think about the change and about the permanent innovation and, the fact is that the new needs and desires of the today demand it is different from what was demanded yesterday.